Ligand‐Directed Modification of Active Matrix Metalloproteases: Activity‐based Probes with no Photolabile Group. Issue 33 (9th July 2021) - Kaminska, Monika; Bruyat, Pierrick; Malgorn, Carole; Doladilhe, Marion; Cassar‐Lajeunesse, Evelyne; Fruchart Gaillard, Carole; De Souza, Mélissa; Beau, Fabrice; Thai, Robert; Correia, Isabelle; Galat, Andrzej; Georgiadis, Dimitris; et al.
Abstract: Activity‐based probes enable discrimination between the active enzyme and its inactive or inactivated counterparts. Since metalloproteases catalysis is non‐covalent, activity‐based probes targeting them have been systematically developed by decorating reversible inhibitors with photo‐crosslinkers. By exploiting two types of ligand‐guided chemistry, we identified novel activity‐based probes capable of covalently modifying the active site of matrix metalloproteases (MMPs) without any external trigger. The ability of these probes to label recombinant MMPs was validated in vitro and the identity of the main labelling sites within their S3 ′ region unambiguously assigned. We also demonstrated that our affinity probes can react with rhMMP12 at nanogram scale (that is, at 0.07 % (w/w)) in complex proteomes. Finally, this ligand‐directed chemistry was successfully applied to label active MMP‐12 secreted by eukaryote cells. We believe that this approach could be transferred more widely to many other metalloproteases, thus contributing to tackle their unresolved proteomic profiling in vivo. Abstract : Activity‐based probes have been designed that react with matrix metalloproteases active sites without any external trigger. These phosphinic pseudo peptide probes displayed a preference for human matrix metalloelastase hMMP‐12 and were capable of selectively labelling human and mouse MMP‐12 in complex proteomes.